A peritoneal defect covered by intraperitoneal mesh prosthesis effects an increased and distinctive foreign body reaction in a minipig model. (January 2021) - Eickhoff, Roman Marius; Kroh, Andreas; Eickhoff, Simon; Heise, Daniel; Helmedag, Marius Julian; Tolba, Rene H; Klinge, Uwe; Neumann, Ulf Peter; Klink, Christian Daniel; Lambertz, Andreas
Background: The incidence of incisional hernia is with up to 30% one of the frequent long-term complication after laparotomy. After establishing minimal invasive operations, the laparoscopic intraperitoneal onlay mesh technique (lap. IPOM) was first described in 1993. Little is known about the foreign body reaction of IPOM-meshes, which covered a defect of the parietal peritoneum. This is becoming more important, since IPOM procedure with peritoneal-sac resection and hernia port closing (IPOM plus) is more frequently used. Methods: In 18 female minipigs, two out of three Polyvinylidene-fluoride (PVDF) -meshes (I: standard IPOM; II: IPOM with modified structure [bigger pores]; III: IPOM with the same structure as IPOM II + degradable hydrogel-coating) were placed in a laparoscopic IPOM procedure. Before mesh placement, a 2x2cm peritoneal defect was created. After 30 days, animals were euthanized, adhesions were evaluated by re-laparoscopy and mesh samples were explanted for histological and immunohistochemichal investigations. Results: All animals recovered after implantation and had no complications during the follow-up period. Analysing foreign body reaction, the IPOM II mesh had a significant smaller inner granuloma, compared to the other meshes (IPOM II: 8.4 µm ± 1.3 vs. IPOM I 9.1 µm ± 1.3, p < 0.001). The degradable hydrogel coating does not prevent adhesions measured by Diamond score (p = 0.46). A peritoneal defect covered by a standard or modified IPOM mesh was a significant factor for increasing foreign body granuloma, the amount of CD3+ lymphocytes, CD68+ macrophages and decrease of pore size. Conclusion: A peritoneal defect covered by IPOM prostheses leads to an increased foreign body reaction compared to intact peritoneum. Whenever feasible, a peritoneal defect should be closed accurately before placing an IPOM-mesh to avoid an excessive foreign body reaction and therefore inferior biomaterial properties of the prosthesis.